PEMENUHAN HAK ANAK PEREMPUAN AKIBAT PERNIKAHAN DINI DI KELURAHAN TANAH SEREAL JAKARTA BARAT: Fulfillment of Women’s Rights Due to Early Marriage in Tanah Sereal Village West Jakarta - Ratu Mutiara Anggraini; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2025)
Early marriage is a phenomenon that still occurs in rural and urban communities. Early marriage is very detrimental, especially for women who marry early. By entering into early marriage, we can see the impact they will face, such as whether the rights they should get are protected or not. In this case, to guarantee rights and provide protection to women, there is the Convention on the Elimination of All Forms of Discrimination Against Women. This research will discuss how to implement the fulfillment of economic, educational and health rights based on CEDAW for women involved in early marriage in Tanah Sereal Village, Tambora District, West Jakarta. From the results of research conducted, women who enter into early marriages in Tanah Sereal Subdistrict, West Jakarta, do not have their economic rights, educational rights and health rights fulfilled. Women and their children tend to suffer the most from early marriages. Fulfillment of women's economic, educational and health rights will be fulfilled if they understand the rights they have and do not engage in early marriage, therefore it is necessary to carry out socialization regarding say no to early marriage and free sex, especially in poor and densely populated areas and schools.